Impact of Design on Emotional, Psychological, or Social Well-Being for People With Cognitive Impairment - Karol, E.; Smith, Dianne (2018)
Aim: The objective of this article is to identify and analyze what is known about characteristics in and around the home that support well-being for those with cognitive impairment. This could provide direction for designers of homes in general, but specifically for designers trying to meet the needs of people with cognitive impairment. Background: It has been established that there is a relationship between psychological well-being and a person’s environment. Research also shows that particular design aspects can reduce the impact of cognitive impairment. However, there is limited design expertise in the Australian housing market to create supportive spaces which will help to reduce the impact of the disability for those with cognitive impairment. Method: A literature review was carried out to determine the extent and details of what is known about the relationship of home design and its impact on emotional, psychological, or social well-being for people with cognitive impairment. Conclusions: The study indicates that researchers in various disciplines understand that pragmatic design inputs such as thermal comfort and adequate lighting are important for people with cognitive impairment. In addition, some researchers have shown or surmise that there are other “intangible” designer-controlled elements that have beneficial impacts on people with cognitive impairment. Details of these intangible elements are sparse, and how much they might improve the quality of life for a person with cognitive impairment is not well understood. Further research is required to meet a growing need.